Fotografias como recursos narrativos nas publicações dos dossiês do patrimônio imaterial - Duailibe, Nayala Nunes (2023)
It is worth considering the importance of photographs for the documentation and recording of various forms of intangible heritage, as well as their relevance in the dissemination and appreciation of the cultural practices and traditions of different groups. This thesis analyzes the use of photographic images as a tool in the construction and representation of heritage, questioning how these images shape the understanding of the meaning of heritage. The thesis also highlights the existing gap regarding the role of photographs in the documentation and preservation of intangible heritage, and how they can be used in the context of public policies. The objectives of the thesis are to identify heritage photographs in the narratives of intangible heritage, to analyze the ethnographic sense of heritage processes in relation to the use of photography, and to demonstrate how photographs are used in the publications of the IPHAN files. The work presents an ethnography, which discusses the aspects of anthropological research, the selection methodology of files and photographic images, as well as the proposal of a method with photographs. In the third chapter, the thesis discusses the use of photographs as narrative strategies in intangible heritage records, highlighting the relationship between photography and Anthropology and the collective memory embodied in images. Analysis of the intangible heritage files is presented, focusing on the Wajãpi and Roda de Capoeira files produced by IPHAN. The objective is to understand how narratives are built through the photographs present in these documents and how cultural forms are recorded. The thesis emphasizes the epistemological dimension of the use of images in intangible heritage and addresses the relevance of public heritage policies that use images as central resources in their approach.